2007
DOI: 10.1590/s0102-67202007000200002
|View full text |Cite
|
Sign up to set email alerts
|

Ingestão pré-operatória de carboidratos diminui a ocorrência de sintomas gastrointestinais pós-operatórios em pacientes submetidos à colecistectomia

Abstract: InTRODUÇÃOA nutrição adequada para o paciente cirúrgico é fundamental para boa evolução clínica e redução de complicações pós-operatórias. Há anos, o jejum pré-operatório noturno para alimentos e água, vem sendo prescrito para os pacientes submetidos à cirurgia eletiva. Operações eletivas geralmente mantêm como rotina, a prescrição de jejum por 6 a 12 horas para os pacientes antes do procedimento. Esse tempo é considerado muito longo do ponto de vista metabólico e nutricional, levando à depleção dos estoques d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 13 publications
0
19
0
9
Order By: Relevance
“…Studies depict that in the patient's perception, this discomfort is intense and results in increased anxiety, dehydration, irritability, weakness and despair (1)(2)(3)(4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies depict that in the patient's perception, this discomfort is intense and results in increased anxiety, dehydration, irritability, weakness and despair (1)(2)(3)(4) .…”
Section: Introductionmentioning
confidence: 99%
“…What is observed in practice in many health institutions, however, is that the patient remains fasting for much longer, reaching a mean of 12 to 16 hours, which causes an increase in metabolic response to trauma following the surgery (2,4,11) .…”
Section: Introductionmentioning
confidence: 99%
“…Randomized study with patients undergoing cholecystectomy compared the traditional fasting at midnight with the consumption of a carbohydrate drink (CHO) two hours before surgery. In the referred study, patients had lower incidence of gastro-intestinal complications and shorter hospital stay after surgery compared to the control group (10) .…”
Section: Discussionmentioning
confidence: 73%
“…The risk of infection in the surgical site increases if associated with hair removal in the surgical site because the microscopic cuts in the skin provide foci for bacterial multiplication (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, preoperative fasting, besides quite uncomfortable and unnecessary, can be harmful by enhancing or perpetuating the organic response to trauma 14 . In 2007 Aguilar-Nascimento et al studied 54 female patients undergoing cholecystectomy who received 200 ml of a drink containing 12.5% carbohydrates (CHO) two hours before the operation and concluded that the preoperative intake of that drink reduced the incidence of postoperative gastrointestinal manifestations (nausea and vomiting) and length of hospital stay 16 . The protocol established in our service advocates the use of the drink enriched with 12.5%carbohydrate two hours before the operation, but the patients remained on average about seven hours without ingesting liquids.…”
Section: Results Results Results Resultsmentioning
confidence: 99%